Legal Protection Toward Justice Collator Witness In Disclosing Narcotics Criminal Actions Related To The Theory Of Justice (Study On Decision Number: 297/Pid.Sus/2020/Pn.Sgm) - M. Wakin Bugi Heru Pr (Syariah: Jurnal Hukum dan Pemikiran, 2022)
The role of witnesses in a criminal act is very important in order to reveal the truth. The existence of a suspect witness (justice collaborator) is an effort in tackling drugs. However, justice collaborators also need legal protection because of their position as witnesses and perpetrators. The purpose of this study is how the legal protection of the perpetrator's witness who cooperates (justice collaborator) in uncovering narcotics crimes is associated with the theory of justice by applying an approach method that uses the positivist conception of legis. Based on the data collected, the rules for applying criminal sanctions for witnesses of perpetrators who cooperate (justice collaborators) have yet to find a clear and definite meeting point. It is regulated in Decision Number 297/Pid.Sus/2020/PN.Sgm that according to the Panel of Judges the defendant during the trial was unable to show facts that could reveal the existence of new actors in his case, let alone the defendant gave convoluted information that could complicate the trial, so that the defendant cannot be declared as a witness to the perpetrator who cooperates (justice collaborator) as stipulated in the Circular Letter of the Supreme Court (SEMA) Number 4 of 2011 concerning the treatment of the Whistle Blower and Justice Collaborator.